Catalytic Performance of Vanadium MIL‐47 and Linker‐Substituted Variants in the Oxidation of Cyclohexene: A Combined Theoretical and Experimental Approach. Issue 8 (17th June 2014) - Vandichel, Matthias; Biswas, Shyam; Leus, Karen; Paier, Joachim; Sauer, Joachim; Verstraelen, Toon; Van Der Voort, Pascal; Waroquier, Michel; Van Speybroeck, Veronique
Abstract The epoxidation of cyclohexene has been investigated on a metal–organic framework MIL‐47 containing saturated V+IV sites linked with functionalized terephthalate linkers (MIL‐47‐X, X=OH, F, Cl, Br, CH3, NH2). Experimental catalytic tests have been performed on the MIL‐47‐X materials to elucidate the effect of linker substitution on the conversion. Notwithstanding the fact that these substituted materials are prone to leaching in the performed catalytic tests, the initial catalytic activity of these materials correlates with the Hammett substituent constants. In general, substituents led to an increased activity relative to the parent MIL‐47. To rationalize the experimental findings, first‐principles kinetic calculations were performed on periodic models of MIL‐47 to determine the most important active sites by creating defect structures in the interior of the crystalline material. In a next step these defect structures were used to propose extended cluster models, which are able to reproduce in an adequate way the direct environment of the active metal site. An alkylperoxo species V+VO(OOtBu) was identified as the most abundant and therefore the most active epoxidation site. The structure of the most active site was a starting basis for the construction of extended cluster models including substituents. They were used for quantifying the effect of functionalization of the linkers on the catalytic performance of the heterogeneous catalyst MIL‐47‐X. Electron‐withdrawing as well as electron‐donating groups have been considered. The epoxidation activity of the functionalized models has been compared with the measured experimental conversion of cyclohexene. The agreement is fairly good. This combined experimental–theoretical study makes it possible to elucidate the structure of the most active site and to quantify the electronic modulating effects of linker substituents on the catalytic activity.